The Diagnostic Value of Cytological Findings in Upper Respiratory Infections - TAHAMİLER, Rauf (Cerrahpaşa Medical Journal, 2014)
Respiratory tract extends from the nose to alveoli. Despite some protective mechanisms respiratory tract is exposed to the external enviroment and thus to the infections. Respiratory tract is faced with about 700-800 antigens in every inspiration. The main factors that affect on system are cold, infectious organisms and various antigens and irritants. Upper respiratory tract organs that are exposed to the irritant agents are: nose, sinuses, pharynx and larynx. In this study, throat secretions of the cases who applied to Ear-Nose-Throat outpatient clinics due to upper respiratory tract complaints, were examined both bacteriological and cytological.